1999
DOI: 10.1274/jmor.16.1
|View full text |Cite
|
Sign up to set email alerts
|

Intracytoplasmic Sperm Injection (ICSI) in Cattle and Other Domestic Animals: Problems and Improvements in Practical Use.

Abstract: Intracytoplasmic sperm injection (ICSI) is the [8][9][10].In human ICSI, high fertilization and pregnancy rates were achieved when a motile spermatozoon was injected after immobilization [6]. Dramatic advances in the treatment of severe male-factor infertility have been achieved by using ICSI, and at present, the technique of ICSI is being widely used in clinical applications for human infertility.In cattle, the first ICSI calves were born in 1990 in Japan [4]. These results showed that bovine embryos produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…However, blastocysts/ 235 cleavage rate in our study (30%) is comparable to that reported by Wei and Fukui [12] (32%) which indicates that a failure in the early post-fertilization events -from fertilization until cleavage-is the main determiner to the successful development after bovine ICSI. Application of additional activation stimuli to the bovine ICSI oocytes have been considered important for decondensation of sperm heads, pronuclear formation, cleavage and embryonic development [8,35]. Since induction of 240 abnormally high frequent and/or prolonged calcium elevation may trigger premature termination of embryonic development [36], the additional activation stimuli better to mimic the mechanism induced during normal fertilization without affecting other oocytes metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, blastocysts/ 235 cleavage rate in our study (30%) is comparable to that reported by Wei and Fukui [12] (32%) which indicates that a failure in the early post-fertilization events -from fertilization until cleavage-is the main determiner to the successful development after bovine ICSI. Application of additional activation stimuli to the bovine ICSI oocytes have been considered important for decondensation of sperm heads, pronuclear formation, cleavage and embryonic development [8,35]. Since induction of 240 abnormally high frequent and/or prolonged calcium elevation may trigger premature termination of embryonic development [36], the additional activation stimuli better to mimic the mechanism induced during normal fertilization without affecting other oocytes metabolic pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Such incorporation of the sperm head into the ooplasm results in release from meiotic arrest of the oocyte. In the case of ICSI, the soluble sperm factors are the only oocyte activation factors, except for the physical stimulation of the injection procedure [37].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is not necessary to employ additional protocols to induce oocyte activation and subsequent embryo development. Nevertheless, it is not the case for some large domestic species, whose development to blastocyst and even more to term is extremely low (reviewed by Horiuchi & Numabe 1999).…”
Section: Oocyte Activation Induced By Regular Fertilization and Spermmentioning
confidence: 99%